PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK UNTUK MENINGKATKAN LITERASI NUMERASI PADA PEMBELAJARAN MATEMATIKA SISWA KELAS III SEKOLAH DASAR - Tantri, Juwita Suwita; Bramianto Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop comic-based learning media and assess its feasibility for enhancing students' numeracy literacy skills. This research falls under the category of Research and Development (R&D) using the ADDIE model. The ADDIE model consists of five stages: 1) analysis, 2) design, 3) development, 4) implementation, and 5) evaluation. The subjects of this study involved 38 third-grade students from SDN Mekar Mukti 02. The results of this research showed an average score of 90.7% from three experts media expert, content expert, and language expert categorizing the media as highly valid. Additionally, the teacher response was 85%, and the student response was 88.9%, both categorized as very good. The effectiveness of the comic-based media was measured through pre-test and post-test results, with an N-gain score of 0.6, falling into the medium category. It can be concluded that the use of comic-based learning media can improve the numeracy literacy skills of third-grade elementary school students.